A study on many customers terminate the services provided by Celcom (M) Bhd The Federal Territory of Labuan / Mohammad Faisal Mohtar - Mohtar, Mohammad Faisal (2006)
In this new decade most telecommunication companies reap better profit than before. They compete with one other in order to get more customers and capture market share. Today economic of Malaysia is more stable and this situation help all the telecommunication operators to grow faster and more successful. With the upbeat domestic economic environment providing the backdrop for private sector growth, the communication and multimedia sector is expected to be amongst the key industry beneficiaries. This is in view of the fact that communications is one of the core facilitators in thriving business conditions. In year 2003, major rationalization occurred in the telecommunications sector, which has set the platform for more focused growth by the companies concerned. 1After Telekom merged with Celcom and Maxis merged with TimeCell acquisition effectively fitted a five to only three major or giant operators in fixed line and cellular line. Cellular phone revenue in year 2003 was RM9.49 billion. Out of that Maxis contributed 47% , Celcom 38% and Digi contributed 15%.